2010
DOI: 10.1042/bj20100589
|View full text |Cite
|
Sign up to set email alerts
|

Cell surface heparan sulfates mediate internalization of the PWWP/HATH domain of HDGF via macropinocytosis to fine-tune cell signalling processes involved in fibroblast cell migration

Abstract: HDGF (hepatoma-derived growth factor) stimulates cell proliferation by functioning on both sides of the plasma membrane as a ligand for membrane receptor binding to trigger cell signalling and as a stimulator for DNA synthesis in the nucleus. Although HDGF was initially identified as a secretory heparin-binding protein, the biological significance of its heparin-binding ability remains to be determined. In the present study we demonstrate that cells devoid of surface HS (heparan sulfate) were unable to interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 51 publications
2
23
1
Order By: Relevance
“…That so many of these proteins bind to heparin suggested that their extracellular activities might depend on cell surface heparan sulfate, which unlike heparin is expressed ubiquitously by virtually all animal cells. Indeed, among the identified proteins, cyclophilin A (23), cyclophilin B (24), and hepatoma-derived growth factor (25) have been shown to interact with heparan sulfate and cause a cellular response. Our attention was drawn to HMGB1 because it consistently showed very high peptide coverage in three proteomic screens, it is one of the major DAMPs released by necrotic cells during tissue injury, and it induces angiogenic and inflammatory responses in endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…That so many of these proteins bind to heparin suggested that their extracellular activities might depend on cell surface heparan sulfate, which unlike heparin is expressed ubiquitously by virtually all animal cells. Indeed, among the identified proteins, cyclophilin A (23), cyclophilin B (24), and hepatoma-derived growth factor (25) have been shown to interact with heparan sulfate and cause a cellular response. Our attention was drawn to HMGB1 because it consistently showed very high peptide coverage in three proteomic screens, it is one of the major DAMPs released by necrotic cells during tissue injury, and it induces angiogenic and inflammatory responses in endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Formation of such complexes could also explain delayed internalization of rINGAP that probably occurs by macropinocytosis, as indicated by the inhibition experiments with wortmannin and cytochalasin D. At present, it is unclear whether rINGAP internalization plays a role in the downstream signaling or whether it only serves the purpose of ligand-receptor degradation once the signaling cascade is initiated. Similar internalization kinetics have been described for hepatoma-derived growth factor, which binds its receptor, and heparan/sulphate proteoglycans (55). As shown for hepatomaderived growth factor, receptor binding initiates downstream signaling, whereas the heparan/sulphate-based internalization, also by macropinocytosis, modulates the strength of the related signaling processes.…”
Section: E922 Mechanisms Of Action Of Ingap Protein and Ingap Peptidementioning
confidence: 66%
“…2). Bound rINGAP forms small clusters and patches on the cell surface resembling the cross-linking of membrane multiprotein complexes described for other ligands (15,31,37,45,55). This is different from a homogenous staining exhibited by CTB (Alexa fluor 594) and transferrin (Texas Red) (both from Invitrogen), which were used as positive markers for caveolin-and clathrin-mediated endocytosis.…”
Section: Ingap-p and Ringap Dose-dependently Increase Proliferation Omentioning
confidence: 99%
“…HDGF appears to activate the PI3K/Akt , and/or ERK (Mao et al 2008, Lee et al 2010) and p38 MAPK pathways (Wang et al 2011). Early bovine IVP embryos show active ERK and p38 MAPK pathways (Madan et al 2005), and the ERK pathway appears to be capable of activating p38 MAPK downstream kinases in the absence of p38 MAPK activity to maintain development, showing functional redundancy.…”
Section: Day 7 Blastocysts (%)mentioning
confidence: 99%
“…We performed proliferation assays with rHDGF in more usual conditions with serum, whereby HDGF bioactivity has been previously shown with fibroblasts not only in other species (Klagsbrun et al 1986, Abouzied et al 2005, Wang et al 2011, but also in defined conditions, as intended for embryo culture. Serum may provide carriers and cofactors necessary for GFs to exert their physiological effects (Francis 2010).…”
Section: Morulae (%)mentioning
confidence: 99%